Renal developmental disturbances and their long-term consequences in female pups from vitamin D-deficient mothers: involved mechanisms. (6th February 2019) - Almeida, L. F.; Francescato, H. D. C.; Silva, R. S.; Silva, C. G. A.; Antunes-Rodrigues, J.; de Paula, F. J. A.; Coimbra, T. M.
Abstract: The mechanisms involved in kidney disturbances during development, induced by vitamin D3 deficiency in female rats, that persist into adulthood were evaluated in this study. Female offspring from mothers fed normal (control group, n =8) or vitamin D-deficient (Vit.D-, n =10) diets were used. Three-month-old rats had their systolic blood pressure (SBP) measured and their blood and urine sampled to quantify vitamin D3 (Vit.D3 ), creatinine, Na +, Ca +2 and angiotensin II (ANGII) levels. The kidneys were then removed for nitric oxide (NO) quantification and immunohistochemical studies. Vit.D- pups showed higher SBP and plasma ANGII levels in adulthood ( P <0.05) as well as decreased urine osmolality associated with increases in urinary volume ( P <0.05). Decreased expression of JG12 (renal cortex and glomeruli) and synaptopodin (glomeruli) as well as reduced renal NO was also observed ( P <0.05). These findings showed that renal disturbances in development in pups from Vit.D- mothers observed in adulthood may be related to the development of angiogenesis, NO and ANGII alterations.